PEMANFAATAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) BAGI SISWA KURANG MAMPU - Ahmed Fernanda Desky (Departemen Sosiologi Universitas Sumatera Utara, 2012)
Abstract School Operational Assistance (BOS) allocation at the school to be right on target that the government declared the policy should not the rest of it in improving the quality of education. But the realization of policy dysfunction BOS fund use should conform to the rules set so that it can be said BOS less on target. Documenting the school performed in assessing socio-economic conditions of students families are less able to just look at it subjectively. The method used in this research is quantitative research by the survey method. Samples were taken at two schools respectively were 70 respondents. The end result in this paper is to assess the school's policy that students are not able to do the school still not 100% on target. Because schools do not perform data collection using concrete indicators of poverty such as data collection conducted by the Central Statistics Agency (BPS) resulting latent dysfunction in BOS funds allocated for poor students. Keywords: Utilization of BOS, Underprivileged Students